Analisis Faktor-Faktor Yang Mempengaruhi Penerimaan Pajak Daerah di Wilayah Kabupaten/kota Karesidenan Surakarta tahun 2014-2021 - Whias Nur Alfaisih; Wikan Budi Utami; M. Hasan Ma'ruf (Jurnal Ilmiah Keuangan Akuntansi Bisnis (JIKAB), 2023)
This study analyses the factors that influence local tax revenue in the Regency / City of Surakarta Residency in 2014-2021 using the variables of population, local revenue and gross regional domestic product (GRDP). The purpose of this study is to determine how the influence of population, local revenue and GRDP on local tax revenue. The sample in this study amounted to 56 data taken using saturated sample technique. The data used in this study are secondary data (time series) from 2014-2021 sourced from the Surakarta Karesidenan Central Bureau of Statistics. Data collection techniques using literature studies and documentation studies. This study uses data analysis methods in the form of normality tests, heteroscedasticity tests, multicollinearity tests and autocorrelation tests. While hypothesis testing uses multiple linear regression analysis, F test, t test, and coefficient of determination. The results showed that population has a negative and significant effect on local tax revenue, while local revenue and GRDP have a positive and significant effect on local tax revenue in the regency / city of Surakarta Residency.